Correlating WattbikePro cycle ergometer tests with field tests during college football preparation period - Kawabata, H.; Matsumoto, N.; Iguchi, Y.; Takeuchi, Y.; Onishi, F.; Ishimura, H.; Yamashita, Y. (American Journal of Sports Science, 2024)
Athletes across various sports perform cycle ergometer tests, because cycle ergometers provide a system for evaluating power and endurance by combining intensity and duration. However, cycle ergometers must be used with consideration for the specific characteristics of the sport in which the athlete seeks to improve performance. This study examined the effectiveness of the WattbikePro cycle ergometer test in comparison with a field test used by many soccer players. The study involved 21 male participants, who were members of a university soccer team. The participants were aged 19.5 ± 0.9 years. With heights and weights of 172.7 ± 4.2 cm and 66.8 ± 3.0 kg, respectively. During the first preparatory phase of their annual training plan, the participants underwent fitness tests, including a 50 m sprint, Cooper test, Counter movement jump (CMJ) test, 6 s peak power test, 30 s sprint test, and 3 min aerobic test. Correlation coefficients between the tests were calculated, and significant correlations were found between the CMJ and 6 s peak power tests (r = 0.73; p < .05) and between the Cooper and 3 min average power tests (r = 0.62; p < .05), indicating that introducing WattbikePro into fitness testing and training is effective for conditioning soccer players.